Analysis of the Implementation of the Measles Rubella (Mr) Immunization Program in Preschool Age Children 3-6 Years in Gorontalo Regency - Andi Akifa Sudirman; Dewi Modjo (Journal of Community Health Provision, 2022)
The purpose of this research is to identify the characteristics that contribute to the effective implementation of a measles rubella (MR) vaccination program in preschool children aged 3-6 years in the Gorontalo District. The purpose of this study is to collect comprehensive data on the implementation of the measles rubella (MR) vaccination program in preschool children, particularly in Limboto District, Gorontalo Regency, as measured by communication, resources, monitoring evaluation, perception, attitude, and anxiety. The research method employed is survey. The stages of the activities are as follows: survey activities on-site, data gathering, and data processing. The research period runs from the start of the year to the conclusion of the implementation year. The statistical analysis revealed a link between communication factors, perceptions, attitudes, and anxieties, but no association between resource variables and assessment monitoring and the execution of the MR vaccination program. Then, the findings of multivariate analysis on each variable are used to create the final modeling that is most closely connected to the application of MR immunization.